Plasters from Different Buildings of the Sacred Precinct of Tenochtitlan (Mexico City): Characterization And Provenance. (12th December 2013) - Miriello, D.; Barca, D.; Pecci, A.; De Luca, R.; Crisci, G. M.; López Luján, L.; Barba, L.
<x xml:space="preserve">Abstract</x> In this work, we present the results of the characterization of 20 lime plaster samples taken from the Sacred Precinct of Tenochtitlan (Mexico City), the ancient capital of the Aztec empire. The samples come from different buildings of this precinct (A, B and D) and from the west façade of phase VI of the Templo Mayor pyramid. The objective of the work is to characterize the plaster samples, to understand the raw materials used, and to evaluate the presence of similarities and differences among the samples in the building techniques and raw materials employed. All the samples were studied with OM, SEM–EDS and LA–ICP–MS. The study provided evidence of the plastering and replastering practice in the same constructive phases. The results of the analyses showed the existence of important similarities and differences among buildings and constructive phases in the Sacred Precinct. In order to understand the provenance of the limestone used in the plasters, the lumps and the binder of the samples were analysed. The results were compared with those of the limestone outcrops located in central Mexico. The provenance study showed that all the limestone used in the construction of the analysed buildings of Tenochtitlan's Sacred Precinct comes from the Tula region.